2005
DOI: 10.1115/1.1894180
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combined Cyclic Stretch and Fluid Shear Stress on Endothelial Cell Morphological Responses

Abstract: Endothelial cells in vivo are normally subjected to multiple mechanical stimuli such as stretch and fluid shear stress (FSS) but because each stimulus induces magnitude-dependent morphologic responses, the relative importance of each stimulus in producing the normal in vivo state is not clear Using cultured human aortic endothelial cells, this study first determined equipotent levels of cyclic stretch, steady FSS, and oscillatory FSS with respect to the time course of cell orientation. We then tested whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 44 publications
1
46
2
Order By: Relevance
“…However, endothelial cells in vivo are constantly subjected to blood flow and shear stress, which may affect their morphological and mechanical properties (17,22,23). Therefore, it is essential to investigate tether extraction from endothelial cells exposed to shear stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, endothelial cells in vivo are constantly subjected to blood flow and shear stress, which may affect their morphological and mechanical properties (17,22,23). Therefore, it is essential to investigate tether extraction from endothelial cells exposed to shear stress.…”
Section: Discussionmentioning
confidence: 99%
“…Phenomenologically, this coupling (of EC morphology with WSS) manifests itself in increasing WSS with changes in EC conformation (6): in vitro, ECs elongate, changing from a polygonal, 'cobblestone' morphology to flattened, elongated ovoids (Figures 2a, 2b), the degree of elongation correlating with the magnitude of the shear stress (7)(8)(9)(10). Note that WSS type, too, is relevant-under oscillatory shear, cultured cells retain a polygonal shape (8) and in vivo, ECs have been shown to orientate to the predominant local flow direction (11), perpendicular to the direction of cyclic stretch (12,13). Such observed behavior -4 -should, of course, emerge from a correct and self-consistent model coupling the endothelial state with flow.…”
Section: Introductionmentioning
confidence: 99%
“…Owatverot, et at. (25) found that unidirectional pulsatile shear stress on cultured human aortic endothelial cells was a stronger stimulus than steady shear for inducing cell orientation. It was observed that pure uniaxial cyclic strain of 2% at 0.…”
Section: Unidirectional Pulsatile Shear Effectsmentioning
confidence: 97%